Hermeneutics, teaching of humanities and teaching activities (Research, Society and Development, 2019)
This article analyse, from the hermeneutic approach, the practice and the teaching performance, as a stimulus for the critical-reflexive thought focused on the teaching-learning process and the world of the student's life. Initially, we present the contributions of Schleiermacher, who established the basis for the foundation of hermeneutics as a universal methodology and applicable to all areas of knowledge; and Dilthey who sought to give a new methodological meaning to hermeneutics, which is more directed towards the promotion and development of humanities research. In the sequence, it is exposed the Gadamer thought that proposed a hermeneutic of the dialogical experience and shows the potential of the hermeneutic dialogue in the practice and teaching action. In this perspective, it is argued that dialogue, in the perspective of philosophical hermeneutics, in the humanities area, stimulates autonomy, critical-reflexive thinking and responsible student performance. Finally, the intention of the study is to show the philosophical / pedagogical potential of the dialogue (question / answer) that is realized and opens new possibilities of teaching, learning and ethical understanding of the other.